Manajemen Asrama di Pesantren - Djamaluddin Perawironegoro (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Pesantren as Islamic education institution have two main focuses in organizing their activities programs; first is the aspect of learning, and second is the aspect of Education. In the Learning aspect, the Santri gained cognitive knowledge from Kitab Kuning book, whereas the Santri obtained the affective and psychomotor aspects through the boarding education system. Where the Santri lives with his friends, teachers, and Kyai together in the scope of Pondok or dormitory. The purpose of writing this paper is to describe dormitory management with a managerial perspective. The conclusion is that the dormitory management concept, which includes planning, organizing, actuating, and controlling, has been carried out by boarding schools. Optimizing the management functions of the management of the dormitory will assist the board in achieving the main objectives of boarding school.